2018
DOI: 10.1038/s41598-018-19476-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-36/LXR axis modulates cholesterol metabolism and immune defense to Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) is a life-threatening pathogen in humans. Bacterial infection of macrophages usually triggers strong innate immune mechanisms, including IL-1 cytokine secretion. The newer member of the IL-1 family, IL-36, was recently shown to be involved in cellular defense against Mtb. To unveil the underlying mechanism of IL-36 induced antibacterial activity, we analyzed its role in the regulation of cholesterol metabolism, together with the involvement of Liver X Receptor (LXR) in this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…1a and Supplementary Data 1). As expected, key IL-36 target genes (IL1B, PI3, VNN2, TNFAIP6, SERPINB1) 15 collectively showed a significant up-regulation in cases vs. controls (P=0.019) ( Fig.1b). Of note, the analysis of a publicly available PsV dataset (whole-blood samples obtained from 33 cases vs 44 controls) 16 identified a moderate, but statistically significant, over-expression of the same genes (P=0.001) ( Fig.1b), providing the first indication that IL-36 may have systemic effects in PsV.…”
Section: Expression Profiling Identifies a Type-i Ifn Signature In Gpsupporting
confidence: 77%
“…1a and Supplementary Data 1). As expected, key IL-36 target genes (IL1B, PI3, VNN2, TNFAIP6, SERPINB1) 15 collectively showed a significant up-regulation in cases vs. controls (P=0.019) ( Fig.1b). Of note, the analysis of a publicly available PsV dataset (whole-blood samples obtained from 33 cases vs 44 controls) 16 identified a moderate, but statistically significant, over-expression of the same genes (P=0.001) ( Fig.1b), providing the first indication that IL-36 may have systemic effects in PsV.…”
Section: Expression Profiling Identifies a Type-i Ifn Signature In Gpsupporting
confidence: 77%
“…Although the protective role of IL-36g against M. tuberculosis through regulation of oxysterol and AP expression has been reported (14,15), the underlying mechanisms are not yet fully elucidated. In this study, we showed a novel, autophagyinvolved bactericidal mechanism of IL-36g in human macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In human PBMCs, in contrast, only APCs but not T cells express IL-36R (13), suggesting the importance of IL-36g in human innate immune regulation. Recently, it was reported that increased IL-36g in macrophages upon M. tuberculosis infection induced several kinds of APs and restricted intracellular M. tuberculosis growth, whereas such effects were attenuated in IL-36R knockdown macrophages (14,15), demonstrating the importance of IL-36g in the control of M. tuberculosis. Therefore, induction of IL-36g expression is important in the host resistance to M. tuberculosis, with unelucidated functional mechanisms.…”
Section: Il-36g Promotes Killing Of Mycobacterium Tuberculosis By Macmentioning
confidence: 99%
“…Indeed, IL-36γ −/− mice exhibited delayed clearance of Streptococcus pneumoniae and Klebsiella pneumoniae in lung infections, decreased Th1 and Th17 cytokine levels, and increased mortality [18]. In Mycobacterium tuberculosis infections, IL-36γ promotes the production of AMPs that limit bacterial growth [13, 26]. In another study, it was found that IL-36R signaling and IL-36α promoted the production of immune mediators and increased influx of neutrophils and monocytes in response to influenza virus infection in the lungs, indicating that the IL-36 cytokines may have distinct functions in response to specific inflammatory stimuli[14].…”
Section: Introductionmentioning
confidence: 99%